238Social gradient of self-rated health in elderly – the moderating/mediating role of sense of community. (2nd September 2021) - Lai, Eric TC; Yu, Ruby; Woo, Jean
Abstract: Background: Social gradients of self-rated health (SRH) of elderly are evident in various settings. However, it is not clear whether improving elderly's sense of community (SoC) could mitigate the social gradient. Methods: Elderly aged 60+ in 5 residential districts of Hong Kong were sampled using multi-stage sampling (n = 1793). SoC was measured using the validated 8-item Brief Sense of Community Scale, with each item on a 5-point Likert scale, forming a score from 8 to 40. SRH was considered as a continuous score from 1 (poor) to 5 (excellent). Socioeconomic status (SES) was operationalized as monthly income, highest education attainment and self-rated disposable income (defined as whether the elderly feels he/she has sufficient income). Causal mediation analysis was used to assess whether SoC mediates/moderates the association of SES and self-rated health. Results: A social gradient of SRH by all measures of SES was observed [b per SD income increase=0.11; 95% confidence interval (95%CI) 0.07 to 0.16; b comparing lowest to highest education=-0.63; 95%CI -0.84 to -0.43; b comparing very sufficient to very insufficient disposable income=-0.76; 95%CI -0.97 to -0.56]. Causal mediation analysis showed that SoC interacts with the association of education and SRH, with higher the SoC stronger the education gradient. SoC mediates the relationship between disposable income and SRH [pure indirect effect=-0.12 (95%CI -0.20 to -0.03). Conclusions: SoC interacts/mediates the associations of education/disposable income and SRH by accentuating them. Key messages: Our findings suggested that improving SoC could not lead to mitigating of social gradient of SRH in the elderly population in Hong Kong.